2016
DOI: 10.18632/oncotarget.9071
|View full text |Cite
|
Sign up to set email alerts
|

Solid tumors provide niche-specific conditions that lead to preferential growth of Salmonella

Abstract: Therapeutic attenuated strains of Salmonella Typhimurium target and eradicate tumors in mouse models. However, the mechanism of S. Typhimurium for tumor targeting is still poorly understood. We performed a high-throughput screening of single-gene deletion mutants of S. Typhimurium in an orthotopic, syngeneic murine mammary model of breast cancer. The mutants under selection in this system were classified into functional categories to identify bacterial processes involved in Salmonella accumulation within tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 78 publications
0
34
0
Order By: Relevance
“…Although the mechanism of bacterial tumor tropism is poorly understood there is evidence indicating that irregular organization of blood vessels within the tumor tissue that often leads to the development of hypoxic and/or necrotic regions and/or an immune-suppressive microenvironment inside the tumor mass may facilitate survival and growth of attenuated auxotrophic bacteria by providing them with nutrients and immune-protection ( Forbes et al, 2003 ; Wouters et al, 2003 ; Yu et al, 2004 ). Moreover, niche-specific genes involved in the process of preferential tumor colonization after systemic bacteria delivery, were also identified ( Silva-Valenzuela et al, 2014 ).…”
Section: Highlights But Still Many Questionsmentioning
confidence: 99%
“…Although the mechanism of bacterial tumor tropism is poorly understood there is evidence indicating that irregular organization of blood vessels within the tumor tissue that often leads to the development of hypoxic and/or necrotic regions and/or an immune-suppressive microenvironment inside the tumor mass may facilitate survival and growth of attenuated auxotrophic bacteria by providing them with nutrients and immune-protection ( Forbes et al, 2003 ; Wouters et al, 2003 ; Yu et al, 2004 ). Moreover, niche-specific genes involved in the process of preferential tumor colonization after systemic bacteria delivery, were also identified ( Silva-Valenzuela et al, 2014 ).…”
Section: Highlights But Still Many Questionsmentioning
confidence: 99%
“…These include entrapment in tumor vasculature; 14 increased influx of bacteria into the tumor site after systemic injection due to inflammation and tumor necrosis factor (TNF)-α response; 16,17 protection from clearance by the immune system; 18 chemotaxis into tumor sites; 19,20 and preferential growth in the nutrient-rich tumor microenvironment. 13,19,21 In our study, we utilized a nonpathogenic strain of Salmonella (VNP20009) that is 10,000-fold less toxic than its wild-type counterpart because of a partial deletion of the msbB gene. 6,22 This mutation reduces the TNF immune response to bacterial lipopolysaccharides and prevents septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have described the ability of Salmonella Typhimurium to sense the concentrations of ethanolamine, a part of membrane lipids, and hence colonize the gastrointestinal tract [ 25 ]. Interestingly, abnormal ethanolamine and other lipid levels of the cell membrane have been detected in different types of neoplasia [ 26 ], and they may be acting as chemoattractants of Salmonella enterica to the tumor [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is controversial data on the role played by certain Salmonella enterica proteins involved in their ability to colonize tumor tissue, particularly the two-component system CheA/CheY; some authors mentioned that the presence of this system is indispensable for effective distribution and bacterial recruitment into tumor tissue [ 23 , 24 , 28 ]; its absence leads to decreased tumor colonization due to lower bacterial motility [ 29 ]. However, other studies have reported that the lack of CheY protein, as well as other bacterial components involved in motility such as the flagellar components fliA, fliC, and flgE, does not compromise Samonella enterica colonization of tumor tissue [ 27 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%